Dynamic Characteristic Optimization of Main Valve in Eight-Speed Auto Transmission Hydraulic Control System - An Y; Liu QH; Gao S (Advances in Mechanical Engineering)
The hydraulic control system has a significant effect on the performance of an automotive transmission system. Conducting a full virtual design and dynamic characteristic optimization of the hydraulic control system parameters during the system development process has a highly significant effect on shortening the development cycle and improving the system performance. This article takes a specific eight-speed auto transmission (8AT) as the control object and, based on the control requirements, principle design of the main circuit, the shift function, and the cooling lubrication system is conducted. In the main pressure regulating circuit, the effect of each structural parameter on the system performance is analyzed by solving the dynamic equations. Further optimal structural parameters for the valve spool are acquired by using a genetic algorithm, and a fluid flow channel simulation the software is Ansys Student 2024 R2 is conducted. The results obtained show that after optimization, the overshoot of the main circuit response is reduced by 18% and the rise time is reduced by 0.08 s; use of the optimal structural parameters of the valve spool can improve the response characteristics significantly.